Cytotoxic, genotoxic/antigenotoxic and mutagenic/antimutagenic effects of the venom of the wasp Polybia paulista - Hoshina, Márcia M. [UNESP]; Santos, Lucilene D. [UNESP]; Palma, Mario Sergio [UNESP]; Marin-Morales, Maria A. [UNESP] (Elsevier, 2013)
Hymenoptera venoms are constituted by a complex mixture of chemically or pharmacologically bioactive agents, such as phospholipases, hyaluronidases and mastoparans. Venoms can also contain substances that are able to inhibit and/or diminish the genotoxic or mutagenic action of other compounds that are capable of promoting damages in the genetic material. Thus, the present study aimed to assess the effect of the venom of Polybia paulista, a neotropical wasp, by assays with HepG2 cells maintained in culture. The cytotoxic potential of the wasp venom, assessed by the methyl thiazolyl tetrazolium assay (MTT assay), was tested for the concentrations of 10μg/mL, 5μg/mL and 1μg/mL. As these concentrations were not cytotoxic, they were used to evaluate the genotoxic (comet assay) and mutagenic potential (micronucleus test) of the venom. In this study, it was verified that these concentrations induced damages in the DNA of the exposed cells, and it was necessary to test lower concentrations until it was found those that were not considered genotoxic and mutagenic. The concentrations of 1ng/mL, 100pg/mL and 10pg/mL, which did not induce genotoxicity and mutagenicity, were used in four different treatments (post-treatment, pre-treatment, simultaneous treatment with and without incubation), in order to evaluate if these concentrations were able to inhibit or decrease the genotoxic and mutagenic action of methyl methanesulfonate (MMS). None of the concentrations was able to inhibit and/or decrease the MMS activity. The genotoxic and mutagenic activity of the venom of P. paulista could be caused by the action of phospholipase, mastoparan and hyaluronidase, which are able to disrupt the cell membrane and thereby interact with the genetic material of the cells or even facilitate the entrance of other compounds of the venom that can act on the DNA. Another possible explanation for the genotoxicity and mutagenicity of the venom can be the presence of substances able to trigger inflammatory process and, consequently, generate oxygen reactive species that can interact with the DNA of the exposed cells. © 2013 Elsevier Ltd.
Keywords: Comet assay; HepG2 cell; Mastoparan and hyaluronidase; Micronucleus test; Phospholipase; DNA; hyaluronidase; mastoparan; mesylic acid methyl ester; phospholipase; wasp venom; cell interaction; concentration response; controlled study; cytotoxicity; DNA damage; enzyme activity; genotoxicity; human; human cell; inflammation; membrane damage; micronucleus test; mutagenicity; Polybia paulista; priority journal; toxicity testing; wasp